Lutetian arc-type magmatism along the southern Eurasian margin: New U-Pb LA-ICPMS and whole-rock geochemical data from Marmara Island, NW Turkey - Ustaomer, P. Ayda; Ustaomer, Timur; Collins, Alan S.; Reischpeitsch, Joerg (SPRINGER WIEN, 2009)
The rocks of Turkey, Greece and Syria preserve evidence for the destruction of Tethys, the construction of much of the continental crust of the region and the formation of the Tauride orogenic belt. These events occurred between the Late Cretaceous and Miocene, but the detailed evolution of the southern Eurasian margin during this period of progressive continental accretion is largely unknown. Marmara Island is a basement high lying at a key location in the Cenozoic Turkish tectonic collage, with a Palaeogene suture zone to the south and a deep Eocene sedimentary basin to the north. North-dipping metamorphic thrust sheets make up the island and are interlayered with a major metagranitoid intrusion. We have dated the intrusion by Laser Ablation ICP-MS analysis of U and Pb isotopes on zircon separates to 47.6 +/- 2 Ma. We also performed major- and trace-elemental geochemical analysis of 16 samples of the intrusion that revealed that the intrusion is a calc-alkaline, metaluminous granitoid, marked by Nb depletion relative to LREE and LIL-element enrichment when compared to ocean ridge granite (ORG). We interpret the metagranitoid sill as a member of a mid-Eocene magmatic arc, forming a 30 km wide and more than 200 km long arcuate belt in NW Turkey that post-dates suturing along the A degrees zmir-Ankara-Erzincan Suture zone. The arc magmatism was emplaced at the early stages of mountain building, related to collision of Eurasia with the Menderes-Taurus Platform in early Eocene times. Orogenesis and magmatism loaded the crust to the north creating coeval upward-deepening marine basins partially filled by volcanoclastic sediments.
Keywords: CORE-COMPLEX-FORMATION; PONTIDE SUTURE ZONE; NORTHWESTERN ANATOLIA; TECTONIC EVOLUTION; WESTERN TURKEY; KARAKAYA COMPLEX; SLAB BREAKOFF; METAMORPHISM; GRANITOIDS; MASSIF; Geochemistry & Geophysics; Mineralogy